Quality of Kefir Combination Between Sweet Corn Milk and Skim Milk on Variations of Sugar Types and Fermentation Duration - Laela Nur Dayanti; Titik Suryani (Quagga: Jurnal Pendidikan dan Biologi, 2025)
This study aims to determine the quality (total acid content and organoleptic quality) of kefir combination between sweet corn milk and skim milk on variations of sugar types and fermentation duration. The research method was experimental, with a completely randomized design (CRD) factorial pattern of 2 factors, namely the sugar types (ant sugar and granulated sugar) and the fermentation durations (36 hours and 48 hours), each treatment of 3 replications. Data analysis was the quantitative and qualitative descriptive methods. The results showed that the quality of kefir combination between sweett corn milk and skim milk was the K2T1 treatment (30 grams of granulated sugar + 36 hours fermentation duration) that was total acid content of 0.92%, pH of 3.83, and the organoleptic quality of slightly sour taste, white color, tasty aroma, smooth and thick texture, and favored acceptability.